2012
DOI: 10.1016/j.jff.2011.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Immunostimulatory effects of water extract from bulbus arteriosus in tuna in vitro

Abstract: Immunoglobulin HB4C5Lactate dehydrogenase Primary lymphocyte A B S T R A C T Immunostimulating effects of water extract from bulbus arteriosus in tuna were examined and found to enhance IgM production by human hybridoma HB4C5 cells. When tuna bulbus arteriosus extract was heated, the IgM production-stimulating activity was decreased or lost. To identify the active substance, the extract was partially purified by anionexchange chromatography, and proteins contained in positive fractions were analyzed by LC-MS/M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 15 publications
0
11
0
Order By: Relevance
“…On the other hand, T cells also play an important role in the cellmediated immunity. We have focused on the foodstuffs that activate the immune system for development of functional foods (Sugahara et al 2005;Nishi et al 2011Nishi et al , 2012Morishige et al 2011;Daifuku et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, T cells also play an important role in the cellmediated immunity. We have focused on the foodstuffs that activate the immune system for development of functional foods (Sugahara et al 2005;Nishi et al 2011Nishi et al , 2012Morishige et al 2011;Daifuku et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…In fact, the homology of primary structures of LDH is fairly close to each other between Oryctolagus cuniculus and Danio rerio (identities = 75 %, similarities = 89 %). In addition, rabbit LDH exerts the immunostimulatory activity on lymphocytes as well as tuna LDH (Daifuku et al 2012a). Thus, LDH from rabbits was used for the experiments described below.…”
Section: Discussionmentioning
confidence: 99%
“…We found that a water-soluble extract from bulbus arteriosus of tuna enhances immunoglobulin (Ig) production by the HB4C5 cells. As for the tuna bulbus arteriosus extract, lactate dehydrogenase (LDH) (EC 1.1.1.27), triosephosphate isomerase (EC 5.3.1.1), enolase (EC 4.2.1.11), and hemoglobin were identified as the active substances (Daifuku et al 2012a). Because LDH showed the strongest Ig productionstimulating activity among these substances on primary spleen lymphocytes from mice, we focused on this enzyme.…”
Section: Introductionmentioning
confidence: 99%
“…In traditional medicine, some herbs are believed to stimulate the immune system, such as ginseng, sage, garlic, elderberry, and hyssop (Brush et al, 2006;Spelman et al, 2006). In our previous studies, some components in foods have been found to stimulate the immune function; for example, lysozyme in hen egg, proteose-peptone component 3 fragment in fermented bovine milk, collagen in jellyfish, ribulose-1,5-bisphosphate carboxylase/oxygenase in kale, tropomyosin in yellowtail hearts, and lactate dehydrogenase and triosephosphate isomerase in tuna bulbus arteriosus increased immunoglobulin (Ig) production by lymphocytes in both in vitro and/or in vivo systems (Daifuku et al, , 2012Murakami, Sasaki, & Sugahara, 1997;Nishi et al, 2011;Sugahara et al, 2005Sugahara et al, , 2006. This suggests that foodstuffs include a variety of substances effective for improving the immune function.…”
Section: Introductionmentioning
confidence: 99%